Chromosome-Level Genome Assembly and Annotation of a Sciaenid Fish, Argyrosomus japonicus. (23rd February 2021) - Zhao, Linlin; Xu, Shengyong; Han, Zhiqiang; Liu, Qi; Ke, Wensi; Liu, An; Gao, Tianxiang
Abstract: Argyrosomus japonicus is an economically and ecologically important fish species in the family Sciaenidae with a wide distribution in the world's oceans. Here, we report a high-quality, chromosome-level genome assembly of A. japonicus based on PacBio and Hi-C sequencing technology. A 673.7-Mb genome containing 282 contigs with an N50 length of 18.4 Mb was obtained based on PacBio long reads. These contigs were further ordered and clustered into 24 chromosome groups based on Hi-C data. In addition, a total of 217.2 Mb (32.24% of the assembled genome) of sequences were identified as repeat elements, and 23, 730 protein-coding genes were predicted based on multiple approaches. More than 97% of BUSCO genes were identified in the A. japonicus genome. The high-quality genome assembled in this work not only provides a valuable genomic resource for future population genetics, conservation biology and selective breeding studies of A. japonicus but also lays a solid foundation for the study of Sciaenidae evolution.